Commercial banks and economic infrastructure PPP projects in Kenya: Experience and prospects - Paul Kamau (Kenya Bankers Association (KBA), 2016)
Infrastructure is an umbrella term for many activities which are referred to as 'social overhead capital' has made many private sector operators shy off from them. This has not been the exception for the banking industry in Kenya. In fact, evidence shows that most of the financing of such infrastructure in Kenya has been through the Exchequer, Roads Maintenance Levy Fund (RMLF), multilateral financial institutions such as the World Bank; the African Development Bank, and donor countries. This paper aims at examining whether commercial banks can benefit from the PPP market in light of evolving opportunities for PPP financing. The broad objective is to explore several aspects of potential benefits that could trigger, improve or diversify the activities of banks in Kenya related to PPP financing. Specifically, the study aimed at finding (a) roles that commercial banks can play; (b) some specifics of the procedure for PPP financing by the banks; (c) trends in participation of banks as lead arrangers on the global PPP market; and (d) presence of international banks in existing PPP projects in Kenya. The paper provides valuable insight to commercial banks as potential financiers of PPP projects in Kenya, as well as provision of financial services. In Kenya opportunities provided by the legal/regulatory framework for public-private partnerships (PPP) are evolving but remain rather novel. The public sector has also not made much headway in accomplishing substantial PPP while private sector stakeholders, including commercial banks are still not actively involved. Commercials Banks, most frequently provide advisory services, and banking services but not financing of PPP projects. With the changing terrains in ownership, financing, operation and management of economic infrastructure in Kenya resulting from the adoption of PPP approach, the Kenyan banking industry has a role to play besides that of credit provision. There is scarcity of knowledge in terms of how the banking industry has been involved in the PPP architecture in Kenya. This study focuses on the road infrastructure. This is because road transport is an enabling industry for almost all other sectors in the Kenyan economy and is critical to the movement and flow of raw materials and finished goods along the agricultural, manufacturing, trade and tourism value chains. In addition, road transport is one of the most widely used modes of transport in Kenya. Road transport has received substantial resources for construction, rehabilitation and maintenance over the past decade and has seen increased role of private industry through PPP, but banks seem to shy away. The findings indicate that most banks have limited participation in the road PPP projects in Kenya. Out of the 71 PPP pipelines currently underway, none of the commercial banks indicated as having participated in any activity. Knowledge about the PPP and opportunities provided for the banking industry seems to be low. Those respondents with knowledge of the annuity programme argued that the financing model was too complicated that it could lead to increased non-performing loans. The paper recommends that there should be more consultative meetings between the banks and the governments in order to promote the partcipation of commercial banks in infrastructure investments. The KBA has to play even a bigger role in mediating between the banking industry and the PPP projects so that banks can commit more resources towards roads PPP projects.
Keywords: 330; Annuity Financing; Infrastructure; Public Private Partnership